Scoring Assessment on Multiple-Choice Questions - Zulpan Zulpan; Sahrul Sahrul; Muhammad Rizky Rochmawan; Arianto Arianto; Ahmad Husein; Ahmad Fauzi Pulungan; Siti Sarah; Tri Idha Sari (Permata Education, 2025)
This article aims to explain the scoring method used in processing the results of multiple-choice tests. The focus of the discussion includes how to construct test items, how to assign scores, how to analyze the results, and how to make decisions based on the test outcomes. The article was developed by conducting an in-depth analysis and synthesis of theories from scientific articles and books related to scoring multiple-choice items. The result is a structured concept that outlines the process of item construction, scoring, and decision-making for multiple-choice tests. This article is expected to assist and facilitate teacher education students and classroom teachers in improving their teaching quality and becoming more professional in their field. The scoring method for test results is generally adjusted to the type of test used, whether it is an objective test, essay test, or other forms. For multiple-choice items, which fall under the category of objective tests, each correct answer is usually assigned a score of 1 (one), while each incorrect answer is assigned a score of 0 (zero).